Introduction: Implications of Recent Changes in Nonmetropolitan America - John R. Sanders (Journal of Research in Rural Education, 1994)
Following the publication of the results of the 1980 census, a spate of articles and reports was published about the status of rural America. A number of these synthesized the economic, social, and political forces impacting nonmetropolitan areas, confirming that dramatic changes were occurring there (e.g., Bender et al., 1985; Jensen & Tienda, 1989; Lazere, Leonard, & Kravitz, 1989). Other articles attempted to draw out the implications of these changes (e.g., Brown & Deavers, 1987; Reid, 1989; Rosenfeld, Bergman, & Rubin, 1989; Stem, 1992). The publication of these works, as well as the think pieces that followed (e.g., Berry, 1986; Haas, 1990; Sample, 1989; Sher, 1988), served to alert the nation that more attention must be given to the condition of rural America. And, it would seem, this literature has informed and helped shape the national, state, and local policy responses apparent in the early years of the decade of the 1990s (e.g., Bhaerman & Van Sciver, 1994; Coe, Kannapel, & Lutz, 1991; Federal Interagency Committee on Education, 1991; McGranahan & Ghelfi, 1991).